Country Partnership Framework for the Republic of Guatemala for the Period FY17-20 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2020)
Guatemala is at an historic juncture, following a political and institutional crisis in 2015, a newly elected government is starting to take on deep-rooted development problems. The crisis was triggered by the uncovering of a corruption scheme that permeated the tax administration superintendence (SAT) and the highest political levels. The country has enormous potential to generate growth and prosperity for its population; yet growth remains low, poverty and inequality persistently high, and high rates of childhood stunting threaten Guatemala’s ability to reach its full development potential. This glaring juxtaposition highlights the existence of two Guatemala’s, with large gaps in both social and economic outcomes. In this context, the World Bank Group’s (WBG) new country partnership framework (CPF) seeks to support Guatemala in fostering inclusion of vulnerable groups, and addressing bottlenecks to sustainable growth.